Second to fourth digits ratio (2D:4D) and subjective pain experience in tattooing - Kozieł, Sławomir; Chakraborty, Raja; Sitek, Aneta (Anthropological Review, 2013)
This aims of this research are to determine if the 2D:4D digit ratio is related to subjective pain experience during tattooing and to examine gender differences therein. The study involved 43 male and 28 female Polish adults recruited from two tattoo salons in Wroclaw and Leszno in Western Poland. These subjects were asked if they felt pain during their tattooing and answers were recorded as ‘Yes’ or ‘No’. The ventral surface lengths of the second and fourth digits of each hand were measured, and analysis of variance was performed to assess significant differences in the 2D:4D ratios of right and left hands and two- hand averages between genders and the Yes/ No groups reporting pain experience. Results revealed that although the digit ratios for females had systematically higher values than those in males, differences were not statistically significant. Both sex and subjective pain feeling were significantly associated with 2D:4D ratio in both hands and their average values, while sex and pain experience were independently associated with digit ratio. Subjects who felt pain during tattooing had a significantly lower digit ratio. In conclusion, the study did not support the hypothesis that the lower masculine 2D:4D ratio is associated with a higher pain threshold. Prenatal sex hormonal exposure generating the gender dimorphic 2D:4D index may not predispose the actual feeling of all kinds of pain; in this instance, not in pain associated with tattooing.